The microstructural evolution and relaxation strengthening for nano-grained Ni upon low-temperature annealing - Ze Chai; Bo Peng; Xukai Ren; Kaiyuan Hong; Xiaoqi Chen (Nano Materials Science)
The microstructural evolution and relaxation strengthening of nano-grained Ni annealed at a temperature range of 493–553 ​K were studied by in situ X-ray diffraction technique, transmission electron microscopy, and microhardness evaluation. Upon low-temperature annealing, the rather limited variations of anisotropic grain size and root-mean-square strain, conforming to an exponential relaxation model, yield a consistent activation energy of approximately 0.5 ​eV, which corresponds to the localized, rapid diffusion of excess vacancies on nonequilibrium surfaces/interfaces and/or defective lattice configurations. Microstructure examinations confirm the grain boundary ordering and excess defect reduction. The relaxation-induced strength enhancement can be attributed to the linear strengthening in the regime of small elastic lattice strains. This study provides an in-depth understanding of low-temperature nanostructural relaxation and its relation to strengthening.